Effects of amines on particle growth observed in new particle formation events. Issue 1 (7th January 2016) - Tao, Ye; Ye, Xingnan; Jiang, Shuqing; Yang, Xin; Chen, Jianmin; Xie, Yuanyuan; Wang, Ruyu
Abstract: Particle size distributions in the range of 0.01–10 µm were measured in urban Shanghai in the summer of 2013 using a Wide‐range Particle Spectrometer (WPS). Size‐segregated aerosol samples were collected concurrently using a Micro‐Orifice Uniform Deposit Impactor (MOUDI), which aided our in‐depth understanding of the new particle formation (NPF) mechanism in the polluted Yangtze River Delta area. During the observations, 16 NPF events occurred at high temperatures (~34.7°C) on clear and sunny days. In the ammonium‐poor PM1.0 (particulate matter less than 1.0 µm), sulfate and ammonium accounted for 92% of the total water‐soluble inorganic species. Six aminiums were detected in these MOUDI samples, among which the group of diethylaminium and trimethylaminium (DEAH +  + TMAH + ) was the most abundant. The very high level of aminiums (average concentration up to 86.4 ng m −3 in PM1.8 ), together with highly acidic aerosols, provided insight into the frequent NPF events. The high mass ratio of total aminiums to NH4 + (>0.2 for PM0.056 ) further highlighted the important role of amines in promoting NPF. The concentration of DEAH +  + TMAH + in new particles below 180 nm was strongly correlated with aerosol phase acidity, indicating that acid‐base reactions dominated the aminium formation in NPF events. The unexpected enhancement of DEAH +  + TMAH + on a nonevent day was attributed to the transportation of an SO2 plume. Our results reveal that the heterogeneous uptake of amines is dominated by the acid‐base reaction mechanism, which can effectively contribute to particle growth in NPF events. Key Points: Size‐resolved particulate amine salts are first characterized in China The frequent NPF events in hot summer might be associated with the abundant amines The mass fraction of amines in new particles was strongly correlated with total aerosol acidity